An investigation into plant (Juncus effusus) biofilter nitrification modelling - Munhemba, Tinashe (Stellenbosch : Stellenbosch University, 2025)
Munhemba, T. 2025. An investigation into plant (Juncus effusus) biofilter nitrification modelling. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/2d2e8b91-da74-4348-b322-9e343ff3d2f5